Genetic Engineering of Mosquitoes Causes Malaria - Nur Afni Maulina Maghfiro; Lidiya Fatmaningsih; Maulidatul Aulia; Ibrahim Bin Said (Journal of Biomedical and Techno Nanomaterials, 2024)
Malaria is still a health problem in the world and in Indonesia in particular. Malaria vector control is an important strategy in efforts to control and eliminate malaria because it is very effective in preventing infection and reducing disease transmission. The CRISPR/Casnuclease system is a potent new genome editing system and tool for species-specific diagnosis, drug resistance research for Plasmodium species, and gene driver for Anopheles population control, according to an assessment of earlier genome editimg techniques. This Anopheles mosquito CRISPR/Cas9 technique on plasmodium has been applied in research to detect malaria parasites by inhibiting their growth throughout the life cycle, allowing evaluation of the effectiveness of antimalarial drugs or vaccines at various stages of the parasite life cycle. In addition, CRISPR/Cas9 in Anopheles mosquitoes allows identification and double-strand breaks in target DNA, which can then be modified through genome changes. So, with the development of gene editing technology, the spread of Anopheles mosquitoes can be controlled and reduced.